Przekształcenie przedsiębiorcy w spółkę kapitałową — praktyczne problemy przedsiębiorstw transportowych - Barancewicz-Paluch, Marzena (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The Act of 25 March 2011 on the reduction of administrative barriers for citizens and entrepreneurs Journal of Laws of 2011 No. 106, item. 622 introduced anumber of amendments, which legislator intended as facilitating business operation in Polish legal and economic reality. The aim and purposes of the Act were correct, however there have occurred some legal defects influencing the transportation branch that should be pointed out. One of the subjects of the regulation was the amendment of the Commercial Companies Code, which introduced the possibility to transform business run by anatural person into acapital company.The general idea of atransformation process, which was supposed to lead individual businesses into capital companies, was to provide statutory succession of rights and obligations of the entrepreneur being transformed, including permits, licenses and concessions. Unfortunately, new regulations did not bring the expected results for transportation companies run by natural persons.The purpose of this article is to present and consider anumber of administrative and practical problems atransport company struggles with if the transformation decision is taken.
Keywords: spółka kapitałowa; firmy transportowe; przedsiębiorca; przekształcenie